2022
DOI: 10.3390/s22218215
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Low-Cost Data Acquisition System on an E-Scooter for Micromobility Research

Abstract: In recent years, cities are experiencing changes in the ways of moving around, increasing the use of micromobility vehicles. Bicycles are the most widespread transport mode and, therefore, cyclists’ behaviour, safety, and comfort have been widely studied. However, the use of other personal mobility vehicles is increasing, especially e-scooters, and related studies are scarce. This paper proposes a low-cost open-source data acquisition system to be installed on an e-scooter. This system is based on Raspberry Pi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
(35 reference statements)
0
9
0
Order By: Relevance
“…Thus, combining several sensors to assemble one IB for real-world or virtual reality data collection can become extremely expensive. Even for low-cost DASs that do not use commercial sensors but require an IB-like assembly, such as the one proposed by Pérez-Zuriaga et al (2022) [ 28 ] (∼€395.00 or ∼$425.00), cost more than BSafe-360 (∼$300.00) without accounting for the bicycle/e-scooter purchase. These costs also hinder the production of multiple units.…”
Section: Discussion Contributions and Limitationsmentioning
confidence: 99%
“…Thus, combining several sensors to assemble one IB for real-world or virtual reality data collection can become extremely expensive. Even for low-cost DASs that do not use commercial sensors but require an IB-like assembly, such as the one proposed by Pérez-Zuriaga et al (2022) [ 28 ] (∼€395.00 or ∼$425.00), cost more than BSafe-360 (∼$300.00) without accounting for the bicycle/e-scooter purchase. These costs also hinder the production of multiple units.…”
Section: Discussion Contributions and Limitationsmentioning
confidence: 99%
“…References Torque control for assisted E-bike [1,2,24,38,39] Instantaneous pedaling torque waveform [4][5][6][7] Pedaling torque component analysis [8][9][10][11][12][13][14] Factors affecting riding [15][16][17][18][19][20][21][22][23][25][26][27][28][29][30][31][32][33][34][35]] Recharge control for assisted E-bike [36,37] To overcome these limitations on existing E-bike assisted torque control, this paper's motivation is to find the best-suited assisted torque considering external loads. It is shown that the overall cycling torque is affected by external loads, including the cyclist's weight, wind resistance, rolling resistance, and the road slope.…”
Section: Categorymentioning
confidence: 99%
“…In (19), ωk−1 is calculated based on the two prior time steps, t k−1 and t k−2 . It is noted that the position interpolation is under the average speed assumption in (19) without instantaneous motor acceleration and deceleration. For E-bike applications, this assumption is still valid during normal cycling conditions.…”
Section: Ratedmentioning
confidence: 99%
See 2 more Smart Citations